Development of communicative and organizing abilities of schoolchildren in the dimensions of advanced education for sustainable development (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the analysis of the problem of thedevelopment of communicative and organizing abilities of the individual in theperiod of maturation. It is proved that the development of communication skillsis a prerequisite for successful socialization. The author notes that theapplication of the model of advanced education for sustainable developmentallows to fill the system of educational and educational influence with personalmeaning. In the plane of this, the features of the development of thecommunicative and organizing abilities of adolescent schoolchildren areanalyzed. The conclusion is made about the need for targeted support of thisprocess in the context of sustainable development education.
Keywords: education, sustainable development, communication abilities, organizational abilities, adolescence